PENGARUH PROFITABILITAS, LIKUIDITAS DAN INFLASI TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN SEKTOR KONSUMSI PRIMER DI BEI DENGAN RISIKO BISNIS SEBAGAI VARIABEL MODERASI - Rafi Aldarma, (2023)
This research is a quantitative study that aims to determine the effect of profitability, liquidity and inflation on dividend policy with the moderating variable being Business Risk in primary consumption sector companies listed on the Indonesia Stock Exchange in 2019 - 2022. This study used 26 companies as samples with purposive sampling method. The method used is Panel Data Regression Analysis and Moderate Regression Analysis (MRA) with the E-Views 12 program. The results of this study indicate that (1) Profitability affects dividend policy, (2) liquidity has no effect on dividend policy, (3) inflation has no effect on dividend policy. 4) Business Risk is able to moderate the effect of profitability on dividend policy, 5) Business Risk is not able to moderate the effect of liquidity on Dividend Policy, 6) Business Risk is not able to moderate the effect of inflation on Dividend Policy. Keywords: dividend policy, profitability, liquidity, inflation, business risk